ANALISIS KELAYAKAN INVESTASI UNTUK PENGEMBANGAN USAHA PADA RUMAH KOS PINANG INDAH - Yuniar, Yuniar; Murtafia, Murtafia (ADMIT: Jurnal Administrasi Terapan, 2024)
Residence is one of the basic needs of humans, including immigrants. Rumah Kos Pinang Indah as a provider of boarding rooms wants to expand its business by increasing its room capacity so that it can rent out more rooms. Increasing room capacity is a form of investment, but before making an investment there are risks that must be borne in the future, so before making an investment it is necessary to analyze the feasibility of the investment. This research aims to analyze the feasibility of investment that will be carried out by Rumah Kos Pinang Indah using a business feasibility study. By using qualitative methods and explaining the results descriptively, the first data source was obtained from primary data, namely interviews and observations, secondly secondary data by reviewing documents ranging from websites, journals, books, e-books and news articles that are closely related to this research. . The results of the research will produce a business feasibility study document containing an investment feasibility analysis if Kost Pinang Indah increases its room capacity in terms of market and marketing aspects, technical and technological aspects, management and organizational aspects to financial aspects.